A dynamic state estimation method for power systems. (13th February 2012) - Jia, Qing–quan; Wang, Ning; Dou, Chun–xia; Bo, Zhi–qian
GPS based Phasor Measurement Units (PMUs) are prevailing in power systems. This paper introduces a dynamic state estimation method for power systems. As installation of PMUs at all buses is impractical, this method employs SCADA data that covers the whole system and PMU data that covers part of the system. The PMU samples are interpolated into the SCADA data to increase the measuring density. An iterative state estimation algorithm is established with the coordination of PMU and SCADA measurements. Example shows that the method can increase the estimating precision and provide more information on power system dynamics.